MANAJEMEN TENAGA PENDIDIK DALAM MENINGKATKAN MANAJEMEN MUTU DI MADRASAH TSANAWIYAH MIFTAHUL ULUM BONDOWOSO - Rosabila Millati Izza Firdausiyah; Fahim Tharaba (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze teacher management in improving the quality of education at Madrasah Tsanawiyah Miftahul Ulum Bondowoso. The research focuses on how the planning, implementation, and evaluation processes of teacher management are carried out and how these processes contribute to school quality improvement. This research employs a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation, and then analyzed naturalistically to obtain an in-depth understanding of the existing phenomena. The findings indicate that teacher management at the madrasah has been implemented fairly well, covering recruitment, placement, professional development, and supervision, although weaknesses remain, particularly in the selectivity of recruitment and alignment between teachers’ competencies and teaching assignments. Furthermore, quality management implementation at the madrasah is realized through collaborative vision–mission planning, strengthened teamwork, and improvement of student outcomes through instructional programs, relevant curriculum use, and optimal utilization of learning facilities. The novelty of this study lies in its finding that the success of quality improvement is strongly influenced by the strength of teamwork and the consistent application of a quality culture through PDCA-based cycles.